ANALISIS IMPLEMENTASI STANDAR KOMPETENSI LULUSAN (SKL) DAN STANDAR ISI (SI) PADA JENJANG SMP: STUDI KASUS DI SMP NEGERI 4 MELAYA, SMP NEGERI 2 TUAL, DAN SMP LABORATORIUM UNDIKSHA - Ni Kadek Krisnadewi; Ni Putu Eka Dewi Rahma Yanti; Ni Putu Diah Setiarini; Ni Wayan Rati; I Wayan Lasmawan (STKIP Subang, 2026)
Educational policy changes through the implementation of the Merdeka Curriculum and the deep learning approach require schools to optimally implement Graduate Competency Standards (Standar Kompetensi Lulusan/SKL) and Content Standards (Standar Isi/SI). SKL and SI are essential components in the educational system because they serve as guidelines for curriculum development, learning implementation, and the achievement of students’ competencies. This study aimed to analyze the implementation of Graduate Competency Standards and Content Standards at the junior secondary school level based on the Regulation of the Minister of Primary and Secondary Education Number 10 of 2025 and Number 12 of 2025. This research employed a qualitative descriptive approach. Data were collected through observations, interviews, and document analysis. The study was conducted at SMP Negeri 4 Melaya, SMP Negeri 2 Tual, and SMP Laboratory Undiksha involving principals, teachers, and students as research subjects. The results showed that the implementation of SKL and SI in the three schools had been carried out effectively and was aligned with the Merdeka Curriculum through a deep learning approach. The implementation of SKL was reflected in the development of attitudes, knowledge, skills, and the integration of the eight dimensions of the graduate profile. Meanwhile, the implementation of SI was evident in curriculum structure planning, learning load arrangements, and the implementation of intracurricular, cocurricular, and extracurricular activities adjusted to learning outcomes and students’ characteristics. Therefore, the implementation of SKL and SI supports the creation of more meaningful, contextual, and holistic learning processes in improving students’ competencies.